The cholesterol-lowering effect of statins is modified by LILRB5 intolerance genotype: Results from a recruit-by-genotype clinical trial - Tornio, Aleksi; Bigossi, Margherita; Siddiqui, Moneeza K.; Kennedy, Gwen; Melhem, Ala’a; Chourasia, Mehul K.; Maroteau, Cyrielle; Pola, Roberto; Chasman, Daniel I.; Doney, Alexander S. F.; Palmer, Colin N. A. (Frontiers in Pharmacology, 2023)
Background/Aims Statin intolerance leads to poor adherence to statin therapy, resulting in a failure to achieve desired cholesterol reduction and adverse outcomes. The LILRB5 Asp247Gly genotype has been identified as being associated with statin intolerance and statin-induced myalgia. We conducted a randomized clinical trial to examine its role in immune response through T regulatory cell aggregation and in achieving cholesterol reduction targets. Methods A double-blind, cross-over, recruit-by-genotype trial was undertaken. A total of 19 participants who had either the Asp247Asp (T/T) genotype or the Gly247Gly (C/C) genotype were recruited to the study. Participants were randomised to receive placebo or atorvastatin 80 mg daily for 28 days. Following a washout period of 3 weeks, they were then switched to the opposite treatment. Biochemical and immunological measurements as well as interviews were performed prior to and after both treatment periods. Within genotype group comparisons were performed using repeated measures Wilcoxon tests. Two-way repeated measures ANOVA with genotype and treatment as factors were used to compare changes in biochemical parameters between groups during placebo and atorvastatin periods. Results Individuals with the Asp247Asp genotype had a greater increase in creatine kinase (CK) compared to those with Gly247Gly genotype in response to atorvastatin (P=0.03). Those with Gly247Gly genotype had a mean non-HDL cholesterol reduction of 2.44 (95% CI:1.59 – 3.29) mmol/L while in Asp247Asp genotype group the mean reduction was 1.28 (95%CI: 0.48 – 2.07) mmol/L. The interaction between the genotype and treatment for total cholesterol (P=0.007) and non-HDL cholesterol response was significant (P=0.025). Immunological assessment showed no significant changes in aggregation of T regulatory cells by genotype. Conclusions The Asp247Gly variant in LILRB5, previously associated with statin intolerance, was associated with differential increases in creatine kinase and total cholesterol and non-HDL cholesterol-lowering response to atorvastatin. These results suggest that the variant could be used to tailor statin treatment where Asp variant carriers are more likely to be both tolerant to statins and achieve better lipid reduction.